Nowhere To Go: Marginality Of Transgenders In Seven Steps Around The Fire By Mahesh Dattani (Journal of Namibian Studies : History Politics Culture, 2023)
This paper makes an attempt to trace out how the marginalisation of transgenders is represented in the play Seven Steps around the Fire by Mahesh Dattani. The play is an attempt to shatter the male hegemony and to represent the subaltern voice of the transgender. The transgenders have a strong impulsive longing to be a part of the mainstream society. However, they are neglected socially, abused verbally and physically and humiliated repeatedly. Hence the play poignantly emphasises that the subaltern remains to be subaltern in spite of a fight against cultural and social domination. The play offers socio- psychological paradigms related to the existence of transgenders. The ‘silence’ and ‘shame’ of the eunuchs find an expression in the play with a sad realisation that they have “nowhere to go”.